Impact of a Mental Toughness Intervention on Goal-Setting in University Students: A Randomized Controlled Study - Farzad, Valiolah; Karami, Abolfazl (KMAN Counseling & Psychology Nexus, 2023)
This study aimed to investigate the impact of a mental toughness training program on the goal-setting abilities. It hypothesized that participants undergoing the mental toughness training would show significant improvements in goal-setting scores compared to a control group receiving no such intervention. The study employed a quasi-experimental design with pre-test, post-test, and follow-up measurements. A total of 40 students were randomly assigned to either an experimental group, which received a comprehensive mental toughness training program, or a control group, which did not receive any intervention. Goal-setting abilities were assessed at three time points using a standardized goal-setting questionnaire. The results indicated significant improvements in goal-setting scores for the experimental group as compared to the control group. Specifically, the experimental group's mean goal-setting scores increased significantly from pre-test to post-test and were maintained at follow-up, demonstrating the training's effectiveness. Analysis of variance with repeated measurements revealed significant effects for time, group, and the interaction between time and group, further validating the positive impact of the mental toughness training. The findings suggest that mental toughness training is effective in enhancing the goal-setting abilities of students. The improvements observed in the experimental group highlight the potential of targeted psychological interventions in fostering key mental skills necessary for academic success.